2020
DOI: 10.1111/jonm.12935
|View full text |Cite
|
Sign up to set email alerts
|

A qualitative descriptive inquiry of the influences on nurses’ missed care decision‐making processes in acute hospital paediatric care

Abstract: Aim: To explore influences on nurses' missed care decision-making processes in acute hospital paediatric care. Background: Many contemporary studies describe the phenomenon of missed care. It is clear that environment and organizational culture influence the nursing activities; however, what influences their decision-making processes has not been investigated. Method: A descriptive qualitative inquiry was performed using semi-structured interviews with paediatric nurses (n = 20) from one Italian paediatric hos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
20
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(20 citation statements)
references
References 43 publications
0
20
0
Order By: Relevance
“…It seems imperative that nurses at pandemic wards are offered continuous education and support tailored to their individual needs in order to enhance their confidence in decision making and to increase patient safety. As revealed in the present study, some nurses worried that their decisions would compromise patient safety, which may challenge nurses’ ethical beliefs as they operate within a strong moral framework guided by their personal and professional values of providing the best possible care ( Bagnasco et al, 2020 ).…”
Section: Discussionmentioning
confidence: 92%
“…It seems imperative that nurses at pandemic wards are offered continuous education and support tailored to their individual needs in order to enhance their confidence in decision making and to increase patient safety. As revealed in the present study, some nurses worried that their decisions would compromise patient safety, which may challenge nurses’ ethical beliefs as they operate within a strong moral framework guided by their personal and professional values of providing the best possible care ( Bagnasco et al, 2020 ).…”
Section: Discussionmentioning
confidence: 92%
“…According to the findings of this study, several factors have been shown to have an impact on MNCs, including demographic factors (gender and education), job satisfaction, burnout/nurse workload, nurse staffing, nurse competence, work environment, and type of nursing care unit. According to the study's findings, female nurses made up more than 80% of those who responded [3], [6], [7], [13], [14], [15], [17], [18], [19], [20], [22], [23], [24]. Although the majority of respondents are educated RNs [2], [3], [7], [12], [13], [18], [22], [24], some studies show that the majority of respondents are diploma holders [6], [14], [17].…”
Section: Type Of Studiesmentioning
confidence: 99%
“…According to the study's findings, female nurses made up more than 80% of those who responded [3], [6], [7], [13], [14], [15], [17], [18], [19], [20], [22], [23], [24]. Although the majority of respondents are educated RNs [2], [3], [7], [12], [13], [18], [22], [24], some studies show that the majority of respondents are diploma holders [6], [14], [17]. The study's findings are as follows several factors, including job satisfaction, burnout, nurse staffing, nurse competence, work environment, type of nursing care unit, and nurse workload, are the root causes of missed nursing care.…”
Section: Type Of Studiesmentioning
confidence: 99%
“…Indeed, it has been found that committing or witnessing errors is a predisposing factor to the onset of stress and burnout (Winning et al, 2018). Nurses also invest heavily in their work and commit very strongly to the child and family (Bagnasco et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, it has been found that committing or witnessing errors is a predisposing factor to the onset of stress and burnout (Winning et al., 2018). Nurses also invest heavily in their work and commit very strongly to the child and family (Bagnasco et al., 2019). At the same time their increased compassion for and close relationships with children and families in their care could serve to offset or prevent burnout (Mersin, İbrahimoğlu, Çağlar, & Akyol, 2020).…”
Section: Introductionmentioning
confidence: 99%